1999
DOI: 10.1111/ocr.1999.2.3.133
|View full text |Cite
|
Sign up to set email alerts
|

Condylar bony change and craniofacial morphology in orthodontic patients with temporomandibular disorders (TMD) symptoms: A pilot study using helical computed tomography and magnetic resonance imaging

Abstract: The present study was performed to investigate how condylar bony changes related to craniofacial morphology. Twenty‐nine subjects (an average age of 18.8) with condylar bony changes were selected from orthodontic patients who had undergone both helical computed tomography (CT) and magnetic resonance imaging (MRI) to evaluate suspected temporomandibular joint (TMJ) internal derangement and condylar bony changes. Craniofacial morphology was assessed with lateral and frontal cephalograms. For each patient, six li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 12 publications
2
25
0
6
Order By: Relevance
“…Severe cartilage reactions were linked to ipsilateral impairment and retrognathic direction of mandibular growth. By verifying how histological condylar cartilage reactions and subsequent ipsilateral retrognathic mandibular growth are linked sequals to surgically created nonreducing TMJ disc displacement during growth in the rabbit model; the present experimental study might contribute to the understanding of the reported clinical association between facial as ymmetry and non-reducing TMJ disk displacement in humans 8,10,20,21,23,25 [ ( ) T D $ F I G ] Table 1.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Severe cartilage reactions were linked to ipsilateral impairment and retrognathic direction of mandibular growth. By verifying how histological condylar cartilage reactions and subsequent ipsilateral retrognathic mandibular growth are linked sequals to surgically created nonreducing TMJ disc displacement during growth in the rabbit model; the present experimental study might contribute to the understanding of the reported clinical association between facial as ymmetry and non-reducing TMJ disk displacement in humans 8,10,20,21,23,25 [ ( ) T D $ F I G ] Table 1.…”
Section: Discussionmentioning
confidence: 98%
“…The condylar cartilage is a biologically unique articular cartilage with an exceptional capacity for adaptive modelling in response to external stimuli 24 . The cellular activity of the cartilage is regulated by various local growth factors 22 and changes in the cartilage's biophysical environment, such as altered articulating function, triggers or impairs their endogenous expression, leading to increased or decreased condylar growth 6,24 .Several clinical studies of facial asymmetry and mandibular retrognathia, have reported an association with coexisting non-reducing TMJ disc displacement in adults as well as in children and adolescents 8,10,20,21,23,25 . Whether the adverse craniofacial growth predisposed for displacement of the TMJ disc or vice versa was clinically unclear, but cause and effect has been established in longitudinal Int.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…The absence of the TMj due to discectomy induces histological changes in the condylar cartilage [11]. several clinical studies on facial asymmetry and mandibular retrognathia in children and adolescents have reported an association of these conditions with coexisting irreducible displacement of the TMj disc [7,15,17,19,20,22]. in animal experiments, TMj disc displacement was shown to induce histological changes in the condylar cartilage and exert a substantial influence on mandibular growth [1].…”
Section: Introductionmentioning
confidence: 99%